2013
DOI: 10.1186/cc13148
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of alveolar macrophages after 3 cardiac surgery and postoperative pneumonia? – an 5 observational study

Abstract: IntroductionPatients undergoing cardiac surgery have an increased risk of postoperative pneumonia. Pulmonary immune dysfunction might be a contributing factor. We therefore determined changes of the surface molecules on alveolar macrophages (AMs). To characterize modulation in patients with pneumonia we correlated these changes to the development of postoperative pneumonia.MethodsAfter ethical approval and written informed consent, 33 patients undergoing elective coronary bypass grafting surgery were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Patients who postoperatively developed pneumonia revealed a stronger reduction of TLR4 expression on alveolar macrophages than patients who did not 93 suggesting that a local cell-mediated immunosuppression in the lung might be a risk factor for postoperative pneumonia. The expression of TLR4 on alveolar macrophages from patients with ARDS is suppressed and, compared with control cells, does not change after ex vivo stimulation of the cells with LPS 94 .…”
Section: Introductionmentioning
confidence: 95%
“…Patients who postoperatively developed pneumonia revealed a stronger reduction of TLR4 expression on alveolar macrophages than patients who did not 93 suggesting that a local cell-mediated immunosuppression in the lung might be a risk factor for postoperative pneumonia. The expression of TLR4 on alveolar macrophages from patients with ARDS is suppressed and, compared with control cells, does not change after ex vivo stimulation of the cells with LPS 94 .…”
Section: Introductionmentioning
confidence: 95%
“…In a prospective study, Chalk et al have also reported a dysfunction of pulmonary macrophages after CPB. In particular, they have described an early impairment of lung cellular immune response, which could promote the development of postoperative pneumonia [6]. Along these lines, a downregulation of human leucocyte antigen-DR antigen (HLA-DR) expression on monocytes and an increase of plasma interleukine (IL)-10 associated with the occurrence of nosocomial infections have been reported [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…42 More recent, Chalk et al 43 found a trend towards intraoperative decreases in TLR-2 and TLR-4 expression on alveolar macrophages in CABG patients diagnosed with postoperative pneumonia. This has already been demonstrated in surgical ICU patients, in whom LPS tolerance was related to worse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%